The association between the serum levels of matrix metalloproteinase 9 and colorectal cancer - Ismar Rašić; Azra Rašić; Goran Akšamija; Svjetlana Radović; Nedžad Šehović (Medicinski glasnik, 2017)
Aim: To determine the serum levels of matrix metalloproteinase 9 (MMP-9) concentration and their association with the stage and histopathologic sizes of colorectal cancer (CRC). Methods: One hundred and two patients with clinically diagnosed and histologically confirmed colorectal cancer ready for surgical treatment were included in the study. In each patient, preoperative peripheral venous blood samples were taken for determination of the concentration of MMP-9 using ELISA immunoassay test. Resected tumour specimens were studied pathologically according to the criteria of the TNM classification. All patients were divided into groups according to the TNM classification. The control group presented 30 subjects of the appropriate age and gender with no family history of cancer, clinical signs of malignancy or inflammatory bowel disease. Results: The serum levels of MMP-9 were progressively increased in patients with CRC reaching the highest value in the fourth stage of CRC. It was also confirmed that the serum concentrations of MMP-9 were significantly higher in patients with pericolonic lymph nodes involvement compared to the patients with no involvement of lymph nodes, 456.4 (445.9-464.7) ng/mL vs. 438.4 (418.4-447.8) ng/mL (p<0.001). Significantly higher serum levels of MMP-9 were found in the patients with metastatic CRC, 458.5 (452.0-468.1) ng/mL compared with the CRC patients without metastasis, 445.8 (436.9-456.5) ng/mL (p<0.001). Conclusion: It was confirmed that serum concentration of MMP-9 presented the significant independent risk factors for the progression of CRC.
Keywords: colorectal cancer; proteolytic enzyme; serum; risk; progression